Assessing the efficacy and impact of management of an invasive species in a protected area: Poa annua on sub‐Antarctic Macquarie Island. (11th March 2019) - Williams, L K; Sindel, B M; Kristiansen, P; Wilson, S C; Shaw, J D
Summary: Plant eradication is difficult, particularly in remote, protected areas. The Southern Ocean Islands are very isolated and highly protected, but the flora contains many alien plants. Small restricted populations have been eradicated, but eradication of established species has proven difficult. A better understanding of the efficacy of control methods at sub‐Antarctic temperatures and their off‐target impacts may increase eradication success. With interest in controlling non‐native Poa annua in the region, we aimed to determine if physical and chemical methods can control P. annua (the sub‐Antarctic biotype) in sub‐Antarctic conditions and examined their impact on native plants. We quantified the effectiveness of physical control methods on P. annua in situ on sub‐Antarctic Macquarie Island through field‐based experiments and assessed their selectivity on P. annua compared with native grasses. We also quantified the effectiveness of several herbicides on P. annua at sub‐Antarctic temperatures and assessed their selectivity on native grasses. Of the four physical disturbance methods tested, none effectively reduced P. annua cover as one‐off treatments. Of the herbicide treatments, glyphosate and trifloxysulfuron sodium were effective and were less damaging to native grass species, indicating potential selectivity. Physical control was of limited effectiveness, but did not affect native species richness. An integrated weed management programme utilising the strategic use of selective herbicides with follow‐up chemical and physical intervention may balance control and biodiversity outcomes. This research highlights the importance of site‐specific testing of control methods and understanding off‐target impacts of control when managing alien plant species in protected areas.